ASALARISIMONLARNING (HYMENOPTERA:APOIDEA) TABIATDAGI VA INSON HAYOTIDAGI AHAMIYATI VA EKOLOGIK ROLI - Elmurodova, M.V. (Actual problems and prospects of the study of the fauna, 2024)
The article (Hymenoptera: Apoidea) covers the importance and ecological role of bee-eaters in nature. The study of the importance of beekeepers allows them to be used more in agriculture.